Quality Control Using Statistical Quality Control (SQC) Approach On Bag Products of UD. FGH - Riski Ardiansyah; Akhmad Wasiur Rizqi; Moh. Dian Kurniawan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
FGH is a Home Industry that produces bags. Statistical Quality Control (SQC) is a problem-solving technique used to monitor, control, analyze, manage, and improve products. SQC has 4 main statistical tools check sheets, histograms, control charts, and cause and effect diagrams. After observing and analyzing the UD. FGH for 6 months, it found that the highest product defects were unkempt stitches (191 products), the second product defects was damaged zippers (180 products), and the last product defects was brand logo damaged (140 products). In total there are 512 defective products from 4700 of the total products. Improvements that need to be made include choosing suppliers that have good quality, providing training to employees so that they can reduce human errors during production and provide adequate rest hours for workers. FGH merupakan Home Industry yang memproduksi tas. Statistical Quality Control (SQC) merupakan teknik penyelesaian masalah yang digunakan untuk memonitor, mengendalikan, menganalisis, mengelola, dan memperbaiki produk. SQC mempunyai 4 alat statistik utama yaitu check sheet, histogram, control chart, diagram sebab akibat. Setelah melakukan observasi dan analisia pada UD. FGH selama 6 bulan ditemukan kecacatan produk yang paling tinggi adalah jahitan tidak rapi sebanyak 191 produk, yang kedua adalah resleting rusak sebanyak 180 produk, dan yang terakhir logo merk rusak sebanyak 140 produk . Jumlah total ada 512 produk cacat dari 4700 dari total keseluruhan produksi. Perbaikan yang perlu dilakukan diantaranya memilih supplier yang memiliki kualitas yang baik, memberikan training kepada pegawai agar bisa mengurangi human error pada saat produksi dan memberikan jam istirahat yang cukup untuk pekerja.